(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Lactic acid bacteria have an important role for the preservation of foods and fermented products owing to its probiotic characteristic, with many species from this bacterial group producing several antibacterial compounds including bacteriocins. Antimicrobial screening of crude bacteriocin of Lactobacillus acidophilus NCDC – 015 was analyze against the selected food pathogen (Bacillus cereus, Listeria monocytogenes, Escherichia coli Staphylococcus aureus, and Salmonella typhi). The inhibitory spectrum evaluated was found to exhibit maximum activity towards gram positive i.e.,Bacillus cereus and Staphylococcus aureus with slight activity for Listeria monocytogenes whereas for gram negatives the crude bacteriocin was ineffective. The two fold arbitrary range for bacteriocin activity with the upper limit of 640 AU/ml against Bacillus cereus and Staphylococcus aureus, with the reduction in the inhibition for Listeria monocytogenesto 40 AU/ml were observed. The results thus give insight of Lactobacillus acidophilus NCDC – 015 as a promising bacterioicin producer possessing antagonistic properties against food - borne pathogens.